Sistem Kepercayaan Monotheisme dalam Praktik Spiritual dan Sosial Masyarakat Sunda Pra Islam - Maulana, Ilham; Syah, Muhammad Kautsar Thariq (Jurnal Artefak, 2025)
The aim of this research is to determine the monotheistic belief system that existed in Sundanese society before the arrival of Islam. The research method used is qualitative research in the form of library research, namely the study of documents related to the Sundanese people's belief system. This research explains that the existence of Sundanese society before the arrival of Islam already adhered to the belief system of monotheism, namely the belief that the one who controls the universe is one God, this belief is connected to the cycle of life and nature. This research identifies key elements in the belief system of Sundanese people before Islam, which includes the concept of spiritual power, places that are considered sacred, and the role of traditional and religious figures in maintaining traditions. The results of this research show that the belief system of monotheism existed in Sundanese society before Islam was integrated and had a big influence on the social structure of people's daily lives, so that the existence of this belief system really became a strong guide and guide, especially for the continuity of life. development of Sundanese society. This research is important to be used as a basic reference for the development of historical science, especially in exploring knowledge about the existence of Sundanese society with its unique characteristics and of course enriching the treasures of cultural history studies in Indonesia.